Characteristics and Determinants of Internal Labor Mobility in Ukraine - Kupets, Olga (Other Social Protection Study, 2012)
Fifth chapter summarizes the findings of empirical studies on determinants of the migration decision of Ukrainians. Sixth chapter examines short-term labor migration including everyday commuting in 2005-2010 and measures its covariates using individual-level Labor Force Survey (LFS) data. Seventh chapter summarizes the main findings and concludes